Opinions of students of Public Health Institute on teaching statistics and informatics Health Self-Assessment in students of Pomeranian Medical University in Szczecin - Panasewicz-Lipczyk, Jolanta; Maniecka-Bryła, Irena (Polish Journal of Public Health, 2010)
Introduction. Considering the significance of informatics and statistics in modern Health Service, it is necessary to get students acquainted with its software and ways of usage. Aim. The goal of the research was to obtain students’ opinions on statistical tools and the usefulness of knowledge and expertise attained during statistics and informatics courses as well as students’ willingness to learn specialized statistical software. Material and methods. The research covered the group of 164 students of the fourth year of extramural studies at the Institute of Health Sciences, Medical University of Łódź in 2009/2010 academic year. Author’s inquiry form was used in the survey. Pearson-Bravais (V) and Yule-Kendall (Q) correlation convergence indexes as well as Czuprow’s (T), Cramer (C) indexes and Pearson (P) contingency index were applied in the statistical analysis. Results. A significant number of students (97.4%) wishes to learn statistical methods, though they not always see the opportunity to implement such knowledge in their professional life. Almost 62% of the students does not know which software is exerted on daily basis in their employing establishment. Seventy-two (72)% of the students wish to attain the knowledge of working with STATISTICA software and just a little fewer (almost 62%) with SPSS. Conclusion. It seems advisable to take action in order to extend the matter and ways of teaching statistics and informatics by increasing the number of hours of computer laboratory classes, as well as considering higher differentiation of education programs of those subjects at particular specialisations in Public Health Institute. Taking into account unequal level of students’ knowledge in terms of statistical tools and computer software, it is reasonable to make them gradually conversant with STATISTICA and SPSS statistical programs.